Data Understanding and Data Visualization with Python - Sciences, AI (Packt Publishing, 2021)
Learn data visualization from scratch About This Video Learn data manipulation and visualization from scratch Master various Python libraries such as NumPy, Pandas, Matplotlib, and so on Create interactive, insightful visualizations In Detail Data visualization has gained a lot of traction resulting from an increased focus on data analytics. To be a successful data scientist, data manipulation and wrangling is not enough. Visualizing data to garner insights is an equally important tool in the data science toolkit. Given the myriad types of data that exist, visualization has become an increasingly important topic. This course will equip you with all the skills you need to successfully create insightful visualizations. The course first starts with the fundamentals of Python. Then, the course teaches you how to use libraries such as NumPy, Pandas, Matplotlib, Seaborn, Bokeh, and so on. Additionally, you will learn data manipulation, which is the step prior to visualization. You will also learn how to plot geographical data using Folium. Each module in the course has practical hands-on mini projects. Hence, you not only learn the theoretical fundamentals of visualizations but also gain essential practical skills. With over 12 hours of content, this is one of the most comprehensive courses you will be doing on data visualization in Python.
Online resource; Title from title screen (viewed March 26, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos